Hubungan Perilaku Pencarian Informasi Dengan Kebutuhan Informasi Mahasiswa Desain Komunikasi Visual Melalui Aplikasi Pinterest - Nasha Nur Zhafarina; Prijana Prijana; Saleha Rodiah (Universitas Negeri makassar, 2025)
This study aims to examine the relationship between information seeking behavior and the information needs of Visual Communication Design (VCD) students through the Pinterest application. VCD students rely on visual information as a source of inspiration and reference in their creative process. The research employed a quantitative method with a correlational approach involving 99 VCD students from Maranatha Christian University selected using simple random sampling. Data were collected through questionnaires and analyzed using the Pearson Product Moment correlation test. The results show that all stages of Ellis’s information-seeking behavior theory have a positive and significant relationship with students’ information needs, including new inspiration, design trends, specific visual, technical, and commercial information. These findings indicate that Pinterest plays an important role as a digital medium that fulfills visual information needs and supports the creative learning process of VCD students.